Living in technical legality : science fiction and law as technology - Tranter, Kieran (Edinburgh critical studies in law, literature and the humanities., 2018)
Through detailed readings of popular science fiction, including the novels of Frank Herbert and Octavia E. Butler and television's Battlestar Galactica and Doctor Who, this is the first sustained examination of legality in science fiction.